2001
DOI: 10.1002/1097-4636(20010905)56:3<400::aid-jbm1109>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Collagen filaments as a scaffold for nerve regeneration

Abstract: This article describes repair of peripheral nerve defect using collagen filaments instead of tubes. Many tube-shaped nerve guides induce regeneration of severed peripheral nerve axons within a limited distance. Substantial regeneration of nerve axons has not been reported without a tubular conduit. Here we show the regeneration of peripheral nerve axons along filaments of collagen without a tube. Cables of collagen filaments were grafted to repair 20-mm defects of rat sciatic nerves. Nerve autografts and colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 25 publications
2
65
0
1
Order By: Relevance
“…In addition, the simultaneous immobilization of bioactive substances is feasible. Our previous study 35, [37][38][39]. The bioactive substances used are laminin and fibronectin, which are cell adhesion proteins and showed that the release of bioactive substances from photogels depends on the degree of swelling of the phowhich accelerate cell migration and proliferation (7,11,17,20,22,30,31,37,38).…”
Section: Electrophysiological Responsesmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the simultaneous immobilization of bioactive substances is feasible. Our previous study 35, [37][38][39]. The bioactive substances used are laminin and fibronectin, which are cell adhesion proteins and showed that the release of bioactive substances from photogels depends on the degree of swelling of the phowhich accelerate cell migration and proliferation (7,11,17,20,22,30,31,37,38).…”
Section: Electrophysiological Responsesmentioning
confidence: 99%
“…Therefore, longitudinally directed growth (10,18,20,27,29,30-32, 38,39). Collagen has been used to fabricate such neurothe combined use of a high surface area and bioactive substances may provide an adequate microenvironment prosthetic devices (6, 16,20,30,31,39).…”
Section: Electrophysiological Responsesmentioning
confidence: 99%
See 3 more Smart Citations